2021
DOI: 10.1371/journal.pone.0247198
|View full text |Cite|
|
Sign up to set email alerts
|

Seasonality, climate change, and food security during pregnancy among Indigenous and non-Indigenous women in rural Uganda: Implications for maternal-infant health

Abstract: Background Climate change is expected to decrease food security globally. Many Indigenous communities have heightened sensitivity to climate change and food insecurity for multifactorial reasons including close relationships with the local environment and socioeconomic inequities which increase exposures and challenge adaptation to climate change. Pregnant women have additional sensitivity to food insecurity, as antenatal undernutrition is linked with poor maternal-infant health. This study examined pathways t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 63 publications
2
28
0
1
Order By: Relevance
“…The predicted trend of drought occurrence is less consistent [ 98 ], but recent evidence suggests that frequency, duration, and intensity have increased in parts of the Americas, Africa, and Asia, and this trend is expected to continue [ 99 , 100 ]. Like hurricanes, droughts lead to water and food insecurity and malnutrition due to reduced access to safe drinking water, massive livestock death, and crop failure [ 101 , 102 ]. In most sub-Saharan African countries where droughts are endemic, more than 20% of women are classified as malnourished, a maternal major risk factors for low birthweight and fetal growth restriction [ 103 ].…”
Section: Direct Impacts Of Climate Change On Pregnancy Outcomesmentioning
confidence: 99%
“…The predicted trend of drought occurrence is less consistent [ 98 ], but recent evidence suggests that frequency, duration, and intensity have increased in parts of the Americas, Africa, and Asia, and this trend is expected to continue [ 99 , 100 ]. Like hurricanes, droughts lead to water and food insecurity and malnutrition due to reduced access to safe drinking water, massive livestock death, and crop failure [ 101 , 102 ]. In most sub-Saharan African countries where droughts are endemic, more than 20% of women are classified as malnourished, a maternal major risk factors for low birthweight and fetal growth restriction [ 103 ].…”
Section: Direct Impacts Of Climate Change On Pregnancy Outcomesmentioning
confidence: 99%
“…Also, according to Patterson et al [24], more than 90% of Batwa households are rated as "very highly food insecure". In 2017, Batwa mothers reported being malnourished and having malnourished children due to a scarcity of food [25].…”
Section: Study Populationmentioning
confidence: 99%
“…Studies conducted in the same area show linkage between environmental factors and maternal and neonatal health. For example, Bryson et al [25] described the link between pregnancy outcomes and climate change in Kanungu District among Indigenous and non-Indigenous populations, highlighting the impact of environmental factors on food security and maternal diet. Also, MacVicar et al [22] found a causal pathway between weather, seasonal variability and birth weight among the same communities.…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…The established underlying causes of malnutrition across all age groups likely follow a seasonal pattern, with consequences for morbidity and mortality across the life cycle (Bryson et al, 2021). Hence establishing the seasonal patterns in food availability and its effect on nutritional health or morbidity have policy implications in planning the distribution of scarce resources.…”
Section: Introductionmentioning
confidence: 99%